Protective effects of zingerone against bisphenol-A induced oxidative stress and apoptosis in SH-SY5Y cells: the role of TRPM2 channel - Cinar, Ramazan; Caglayan, Cuneyt; Yardimci, Mahmut; Yildizhan, Kenan (Springer, 2026)
BackgroundBisphenol A (BPA) is a common environmental endocrine disruptor that causes oxidative stress and neuronal damage. However, the role of redox-sensitive ion channels, such as TRPM2, and potential protective interventions have not been thoroughly explored. This study provides novel mechanistic insight into TRPM2-mediated neuronal damage and highlights the potential of zingerone (ZG) as a natural therapeutic strategy against environmental neurotoxicity.MethodsThe cells were exposed to BPA (250 & micro;M) with or without ZG (25 & micro;M) for 24 h. We assessed cell viability (CCK-8), oxidative stress parameters (MDA, ROS, GSH, and GSHPx), inflammatory cytokines (IL-1 beta, IL-6, and TNF-alpha), apoptotic caspases (3, 8, and 9), and TRPM2/PARP-1 expression using ELISA and Western blotting.ResultsExposure to BPA significantly reduced cell viability and triggered oxidative imbalance, inflammation, and apoptosis, as well as upregulation of TRPM2. In contrast, co-treatment with ZG restored antioxidant defences, suppressed cytokine release, inhibited caspase activation, and downregulated PARP-1/TRPM2 signaling.Conclusions These results suggest that ZG protects against BPA-induced neuronal damage by regulating PARP-1/TRPM2-associated redox signalling pathways and provide further evidence for TRPM2's involvement in environmental neurotoxicityGraphical abstractProtective effect of ZG against BPA-induced neurotoxicity in SH-SY5Y cells. BPA induces oxidative stress, inflammation, apoptosis, and TRPM2 activation, whereas ZG attenuates these effects by modulating the PARP-1/TRPM2-dependent redox signalling pathway, thereby enhancing cell survival.
Keywords: Zingerone; Bisphenol A; Oxidative Stress; Trpm2 Channel; Neuroprotection